Cdc14 phosphatase directs centrosome re-duplication at the meiosis I to meiosis II transition in budding yeast [version 2; referees: 3 approved, 1 approved with reservations] - Colette Fox; Juan Zou; Juri Rappsilber; Adele L. Marston (Wellcome Open Research, 2017)
Background Gametes are generated through a specialized cell division called meiosis, in which ploidy is reduced by half because two consecutive rounds of chromosome segregation, meiosis I and meiosis II, occur without intervening DNA replication. This contrasts with the mitotic cell cycle where DNA replication and chromosome segregation alternate to maintain the same ploidy. At the end of mitosis, cyclin-dependent kinases (CDKs) are inactivated. This low CDK state in late mitosis/G1 allows for critical preparatory events for DNA replication and centrosome/spindle pole body (SPB) duplication. However, their execution is inhibited until S phase, where further preparatory events are also prevented. This “licensing” ensures that both the chromosomes and the centrosomes/SPBs replicate exactly once per cell cycle, thereby maintaining constant ploidy. Crucially, between meiosis I and meiosis II, centrosomes/SPBs must be re-licensed, but DNA re-replication must be avoided. In budding yeast, the Cdc14 protein phosphatase triggers CDK down regulation to promote exit from mitosis. Cdc14 also regulates the meiosis I to meiosis II transition, though its mode of action has remained unclear. Methods Fluorescence and electron microscopy was combined with proteomics to probe SPB duplication in cells with inactive or hyperactive Cdc14. Results We demonstrate that Cdc14 ensures two successive nuclear divisions by re-licensing SPBs at the meiosis I to meiosis II transition. We show that Cdc14 is asymmetrically enriched on a single SPB during anaphase I and provide evidence that this enrichment promotes SPB re-duplication. Cells with impaired Cdc14 activity fail to promote extension of the SPB half-bridge, the initial step in morphogenesis of a new SPB. Conversely, cells with hyper-active Cdc14 duplicate SPBs, but fail to induce their separation. Conclusion Our findings implicate reversal of key CDK-dependent phosphorylations in the differential licensing of cyclical events at the meiosis I to meiosis II transition.